Struktur Komunitas Ekosistem Pesisir (Lamun dan Mangrove) di Desa Sulamu Nusa Tenggara Timur - Ariandini, Yovita; Faiqoh, Elok; Hendrawan, I Gede (Universitas Trunojoyo Madura, 2021)
East Nusa Tenggara Province (NTT) is an archipelago province located in the south of Indonesia has a sea area of 200,000 km2 (outside ZEEI) in it has marine resources and fisheries that can be developed for the benefit of the community. Seagrass and mangrove ecosystems play an important role for the environment both physically and ecologically. To know the condition of the ecosystem, it is necessary to conduct research on the community structure of seagrass and mangrove ecosystems. This research was conducted in Sulamu Village, Kupang waters in November 2018. Each ecosystem is sampling as many as 3 stations with 3 stations each. From the results obtained, found 7 species of seagrass in salamu village waters namely Halodule pinifolia, Thalassia hemprichii, Cymodocea serrulate, Enhalus acoroides, Halophila ovalis, Cymodocea rotundata, and Halodule uninervis. Seagrass density obtained is the highest 2847 tgk/m2 and the lowest 1392 tgk/m2 with stable community conditions. In mangrove ecosystems found 11 types of mangroves found in sulamu waters namely Avicennia alba, Osbornia octodonta, Bruguiera parviflora, Aegiceras corniculatum, Rhizopora mucronata, Sonneratia alba, Rhizopora apiculata, Xylocarpus granatum, Limnitzera racemosa, Gymnanthera paludosa and Nypa frutican. The mangrove community structure in the waters of Salamu Village is unstable and dominating.